Mastering Entity Framework Core 2.0 : Dive into entities, relationships, querying, performance optimization, and more, to learn efficient data-driven development /: Dive into entities, relationships, querying, performance optimization, and more, to learn efficient data-driven development. (2017) - Anbazhagan, Prabhakaran
No abstract available